Development of Subject-Specific Pedagogy for Natural Science Based on the MIKiR Approach for Landslide Disaster Prevention - Prastyo, Erwin; Lengkana, Dewi; Setiadi, Heri (Jurnal Komunikasi Pendidikan, 2023)
Students' lack of a disaster response mindset is both a problem and a challenge that must be addressed in science education. Based on the MIKiR approach, which is linked with natural disaster prevention, the goal of this study is to define the features of science Subject-Specific Pedagogy. This study involves both research and development (R&D). The research procedure follows the Borg & Gall development model, which involves five main steps: (1) analyzing the product to be developed; (2) developing the initial product; (3) expert validation and revision; (4) small-scale field testing and revisions; and (5) large-scale field testing and final products. A validation sheet with a Likert scale in the form of a checklist serves as the research instrument. According to the study's findings, the quality of the developed Subject-Specific Pedagogy is listed in the good category, with an optimum proportion of 84.33 percent. The findings of the study on product quality could be used as one of the science learning aids in SMP/MTs class IX semester 2.